Neuroprotective mechanisms of rutin for spinal cord injury through anti-oxidation and anti-inflammation and inhibition of p38 mitogen activated protein kinase pathway - Hong-liang Song (Neural Regeneration Research, 2018)
Rutin has anti-inflammatory, antioxidant, anti-viral, anti-tumor and immune regulatory effects. However, the neuroprotective effects of rutin in spinal cord injury are unknown. The p38 mitogen activated protein kinase (p38 MAPK) pathway is the most important member of the MAPK family that controls inflammation. We assumed that the mechanism of rutin in the repair of spinal cord injury is associated with the inhibition of p38 MAPK pathway. Allen's method was used to establish a rat model of spinal cord injury. The rat model was intraperitoneally injected with rutin (30 mg/kg) for 3 days. After treatment with rutin, Basso, Beattie and Bresnahan locomotor function scores increased. Water content, tumor necrosis factor alpha, interleukin 1 beta, and interleukin 6 levels, p38 MAPK protein expression and caspase-3 and -9 activities in T8–9 spinal cord decreased. Oxidative stress related markers superoxide dismutase and glutathione peroxidase levels increased in peripheral blood. Rutin exerts neuroprotective effect through anti-oxidation, anti-inflammation, anti-apoptosis and inhibition of p38 MAPK pathway.